PENGEMBANGAN SISTEM PAKAR BERBASIS WEBSITE MENGGUNAKAN METODE CERTAINTY FACTOR UNTUK MENDIAGNOSIS PENYAKIT SISTEM PENCERNAAN MANUSIA DI PUSKESMAS SELAJAMBE - jaenal gopur asmanul salam; Tika (Jurnal Fakultas Teknik Kuningan, 2022)
Lack of public knowledge about gastrointestinal diseases can result in mishandling of treatment of these diseases. Many people do not understand in choosing food for people with gastrointestinal diseases. People don't know enough to avoid food or what is recommended to be consumed by people with gastrointestinal diseases. The wrong selection of food can provoke a recurrence of the disease and it is to cure. The expert system in this study uses the certainty factor method, which is a method that defines a measure of certainty of a fact or rule, to provide the value of expert certainty to the problem at hand. This expert system is web-based, thus users can easily access the application. Data were collected by interview method and literature study. The research was conducted using the Waterfall method. The conclusion obtained is that the expert system using the CF (Certainly Factor) method can make it easier for patients to initially diagnose the type of stomach ulcer based on the symptoms experienced by the patient. Keywords: Expert System, Certainty Factors, Gastrointestinal Diseases, Website